An Optimization and Adjustment Method of Pile Orientation for a Pile-Supported Wharf Based on a Genetic Algorithm - Guan-Chen Cui; Ting Liang; Guo-Feng Han (Advances in Civil Engineering)
The pile-supported wharf is widely used in port wharf design due to its excellent adaptability. However, it may intersect in space because a large number of batter piles are used. In the design process of the pile-supported wharfs, pile orientation adjustment is an essential process to avoid pile intersection. The arrangement of pile orientation in a structural section often takes several days manually. Sometimes, designers cannot avoid pile intersections after many attempts. At present, the software can only check pile intersections, but it cannot optimize pile orientations. Considering the priority order of adjusting the pile slope, the rotation angle, and avoiding a pile intersection, the objective function for optimization is designed, and the pile orientation is optimized and adjusted by a genetic algorithm. Then the performance of the algorithm is analyzed. Finally, the algorithm is applied to two practical cases of pile-supported wharfs. One case involves the designers who failed to arrange the pile orientation. Moreover, satisfactory results of pile orientations are obtained in a few minutes. Therefore, the proposed method greatly improves labor efficiency.